Alopecia totalis and vitiligo in common variable immunodeficiency. Issue 785 (March 1991) - Spickett, G.; Prentice, A. G.; Wallington, T.; Webster, A. D.; Chapel, H.
Abstract : Three cases of severe and irreversible alopecia occurring in patients with common variable immunodeficiency are described. In all three cases, hair loss developed after the diagnosis of immune deficiency; one of the patients also had extensive vitiligo. A fourth patient had vitiligo in the absence of alopecia. No change in the alopecia or vitiligo was noted in any patient as a result of immunoglobulin replacement therapy.